Wstrzymanie wykonania orzeczenia w postępowaniu karnym - Nowicki, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In the article, the author presented the issues related to the enforceability of a judgement in criminal proceedings. These issues play an important role, having an impact on the achievement of the objectives of the proceedings and the legal position of the Parties involved. To achieve the indicated goal, it is necessary to present the regulations setting out the principles for handling criminal decisions and to indicate the exceptions provided for by legislation. It was also necessary to provide an assessment of currently functioning solutions. The issues related to the execution of some of the decisions in the course of the criminal proceedings as well as issues related to activities undertaken after its termination were discussed. To illustrate the issues discussed, issues related to recent amendments to the Executive Penal Code relating to the enforceability of judgements were analysed.
Keywords: judgement; enforceability; procedural guarantees; criminal proceedings